THE FLABELLATE-LEAVED SPECIES OF SALACCA (PALMAE) - JOHANIS P. MOGEA (Research Center for Biology, 1980)
Salacca dransfieldiana Mogea,S. magnifica Mogea and S. sarawak ensis Mogea are proposed as new species of flabellate-leaved Salacca.A key to the four recognized species, descriptions and illustrations are presented.